ChemInform Abstract: Regioselective Iodination of Flavonoids by N‐Iodosuccinimide under Neutral Conditions. Issue 13 (1st April 2014) - Lu, Kui; Chu, Jie; Wang, Haomeng; Fu, Xiaoli; Quan, Dewu; Ding, Hongxia; Yao, Qingwei; Yu, Peng
Abstract The iodination can be conveniently directed to either the C‐6 or C‐8 position by changing the protection pattern at the C‐5 OH group.